Use of a numerical simulation approach to improve the estimation of air-water exchange fluxes of polycyclic aromatic hydrocarbons in a coastal zone. Issue 1 (15th July 2017) - Lai, I-Chien; Lee, Chon-Lin; Ko, Fung-Chi; Lin, Ju-Chieh; Huang, Hu-Ching; Shiu, Ruei-Feng
Abstract: The air-water exchange is important for determining the transport, fate, and chemical loading of polycyclic aromatic hydrocarbons (PAHs) in the atmosphere and in aquatic systems. Investigations of PAH air-water exchange are mostly based on observational data obtained using complicated field sampling processes. This study proposes a new approach to improve the estimation of long-term PAH air-water exchange fluxes by using a multivariate regression model to simulate hourly gaseous PAH concentrations. Model performance analysis and the benefits from this approach indicate its effectiveness at improving the flux estimations and at decreasing the field sampling difficulty. The proposed GIS mapping approach is useful for box model establishment and is tested for visualization of the spatiotemporal variations of air-water exchange fluxes in a coastal zone. The air-water exchange fluxes illustrated by contour maps suggest that the atmospheric PAHs might have greater impacts on offshore sites than on the coastal area in this study. Graphical abstract: Highlights: Numerical approach is proposed to improve the air-water exchange flux estimation. Gaseous PAH level is a vital factor in magnitude and direction of diffusive flux. Contour maps suggested the offshore site is sensitively affected by gaseous PAHs. Typhoon occurrence alters PAH distribution between gaseous and aquatic phases.